Dysphagia among Middle-Aged Females - Nudrat Khalil, Mirza Khizar Hameed, Iftikhar Aslam, Irshad Ali, Amir Akbar, Mahum Khizar (Journal of Rawalpindi Medical College, 2022)
Objective: To assess the association of dysphagia with iron deficiency anemia in female patients. Study Design: Descriptive Study Setting & Duration: Department of ENT at Fauji Foundation Hospital Rawalpindi from April 2019 to April 2021. Material and Methods: Approval of the study was obtained from the Hospital Ethical Committee and then Informed Consent was obtained from all the patients. A total of 42 female patients with dysphagia were selected by Consecutive convenient sampling. After detailed history and physical examination, Complete Blood Count and X-ray Barium Swallow were done in all these patients, followed by Rigid Endoscopy under GA. Tissue biopsy was done in all the patients from suspicious areas. The data was analyzed for frequencies by SPSS 24. Results: 42 female patients were included in this study. The mean age of these patients was 46.30 years, ranging from 32 to 65 years. 40 (95%) of these patients showed Esophageal webs in the cricopharyngeal region, while 2 (5%) of them had irregular strictures in the post cricoid region of Hypopharynx. Iron deficiency anaemia was found in 32 (76.19%) patients. Histopathology report showed Squamous Cell Carcinoma in 2 patients with post cricoid strictures, while the rest 40 with webs showed chronic inflammation with fibrosis. Rigid esophagoscopy with web dilatation was highly effective procedure for treatment in 40 (95%) patients. Repeated dilatations were needed in 14 (33%) of the patients. The 2 patients with malignancy underwent Chemo-radiotherapy. Conclusion: Iron deficiency anemia has a strong association with dysphagia in middle age female patients and is a potential risk factor for malignant transformation. Timely diagnosis and prevention of anaemia may result not only in decrease in PVS but also a decreased incidence of hypopharyngeal carcinoma in the vulnerable population. Key words: Dysphagia, Iron deficiency anemia, Post cricoid Carcinoma.